Diagnostic challenges in presumably endogeneous fungal endophthalmitis - Burek, Alicja; Turno-Kręcicka, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Endogenous fungal endophthalmitis is a vision-threatening condition. Fungi are responsible for most cases of endogenous endophtalmitis, with intravenous catheters, bladder catheters, parenteral nutrition, abdominal surgery, long-term use of steroids and antibiotics, as well as immunosuppressive therapy known as its predisposing factors. Three cases of endogenous endophthalmitis in patients with predisposing factors.